2013
DOI: 10.1002/uog.12548
|View full text |Cite
|
Sign up to set email alerts
|

Use of spatiotemporal image correlation at 11–14 weeks' gestation

Abstract: Objective To assess prospectively the use of fourdimensional (4D) spatiotemporal image correlation (STIC) in the evaluation of the fetal heart at 11-14 weeks' gestation. Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 28 publications
2
36
0
Order By: Relevance
“…We evaluated the volume quality referenced in the scoring system by Goncalves et al [20] and found that the mean score for the third trimester was significantly lower than the second trimester. The detection rate was likely correlated to volume quality, which was consistent with previous report [33]. As a retrospective study, we did not evaluate the acquisition quality as some factors (i.e., fetal movement) were not recorded.…”
Section: Discussionsupporting
confidence: 85%
“…We evaluated the volume quality referenced in the scoring system by Goncalves et al [20] and found that the mean score for the third trimester was significantly lower than the second trimester. The detection rate was likely correlated to volume quality, which was consistent with previous report [33]. As a retrospective study, we did not evaluate the acquisition quality as some factors (i.e., fetal movement) were not recorded.…”
Section: Discussionsupporting
confidence: 85%
“…When the volume data set is suboptimal, subsequent analysis will be hindered by low image quality and artifacts. Indeed, investigators have demonstrated that: (1) the ability to visualize fetal cardiac structures is correlated with STIC volume quality 127 ; (2) a positive correlation exists between the “acquisition condition score” (score assigned to fetal movements, ROI setting, acquisition angle, cardiac apex position, and shadowing) and “quality” of STIC volumes 36 ; specifically, the higher the acquisition condition score, the better the volume “quality” (based on the ability to display cardiac structures); and (3) in a multicenter study of 4D fetal echocardiography in the first trimester, centers that reviewed a higher (versus lower) percentage of suboptimal STIC volumes had lower accuracy for identifying CHD 22 …”
Section: Importance Of Acquiring High‐quality Stic Volumes and Influementioning
confidence: 99%
“…It is noteworthy, however, that volumes of superior quality can still be obtained throughout the third trimester, even up to 39 weeks' gestation 90 . Moreover, in the first and early second trimesters, a detailed evaluation of both normal and abnormal fetal hearts using STIC technology can be performed 22 , 47 , 49 , 127 , 131 , 137 . This fact is clinically relevant, due to the increasing role of first‐trimester fetal cardiac examination 138 143 (eg, increased nuchal translucency thickness in the presence of a normal fetal karyotype).…”
Section: How To Perform 4d Sonography With Sticmentioning
confidence: 99%
See 1 more Smart Citation
“…A solid body of evidence suggests that 4D sonography with STIC facilitates examination of the fetal heart 3 , 4 , 5 , 11 37 and may also be used to evaluate fetal cardiac function 18 , 22 , 27 , 30 , 31 , 33 , 38 46 . This modality has also been used in the prenatal evaluation and diagnosis of congenital heart disease (CHD) 2 , 20 , 47 71 because it improves the ability to identify complex intracardiac relationships and can shorten the examination time 3 , 17 , 72 . These facts are important, since evaluation of the normal and abnormal fetal heart 73 75 using 2D sonography is one of the most challenging tasks in prenatal diagnosis.…”
Section: How To Perform 4d Sonography With Sticmentioning
confidence: 99%